2016
DOI: 10.1016/j.foodhyd.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

In situ rheological measurements of the external gelation of alginate

Abstract: Direct mixing of alginate and divalent cations such as Ca 2+ generally produces heterogeneous gels that form almost instantaneously. Therefore, is particularly difficult to measure the rheological properties of this gelation event due to the rapid gelation kinetics. In this study, the gelation of alginate when exposed to a solution of CaCl 2 was measured by using a modified rheometer. This modification involved attaching a petri dish to the lower plate of the rheometer into which, filter paper impregnated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…These observations implied that when a dynamic load is applied, the Fe 3+ -SG hydrogels have a strong physical gel structure, indicating a highly elastic response with a comparatively small dissipation in energy [35,36]. In addition, the slope of G' of the Fe 3+ -SG hydrogel is close to zero, which indicated that the storage modulus and angular frequency were associated with the dynamics of the hydrogel network [37]. Succinolgycan also coordinated with Fe 2 + , thus, high concentrations of Fe 2+ ions would be expected to increase the storage modulus and became a gel.…”
Section: Rheological Measurementsmentioning
confidence: 86%
“…These observations implied that when a dynamic load is applied, the Fe 3+ -SG hydrogels have a strong physical gel structure, indicating a highly elastic response with a comparatively small dissipation in energy [35,36]. In addition, the slope of G' of the Fe 3+ -SG hydrogel is close to zero, which indicated that the storage modulus and angular frequency were associated with the dynamics of the hydrogel network [37]. Succinolgycan also coordinated with Fe 2 + , thus, high concentrations of Fe 2+ ions would be expected to increase the storage modulus and became a gel.…”
Section: Rheological Measurementsmentioning
confidence: 86%
“…Neither of these methods, however, offers suitable experimental simulation of rapid gelation behavior in physiological conditions. Recently in our laboratories, we have demonstrated the experimental monitoring of the external gelation of alginate by modifying a commercially available rheometer . In this paper, we have explored the potential of this modification, as an experimental simulation of in situ gelation on exposure to simulated physiological environments using gellan gum as a model in situ gelling delivery system ( Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, changing the development speed on a machine with a subtractive technology, the surface roughness alteration does not modify the mechanical characteristics, but using the additive manufacturing technology to realise cake decorations, its morphology changes, with the functional aim of the object (aesthetics). Thus, the assessment of the parameters is directly related with the functionality of the 5D object and in the case of the soft tissue development we have to take in consideration drops accidentally falling down or the creation of vascular channel to bring, where required, the gelation fluid for the morphology long-term fixation and dedicated tests 33,34,[36][37][38][39][40][41] are required to better explore any manufactured object and each possible customisation.…”
Section: Discussionmentioning
confidence: 99%